2005
DOI: 10.1111/j.1469-8986.2005.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological correlates of anticipatory task‐switching processes

Abstract: Recent studies show a differential switch-related positivity emerging before a switch trial and reflecting anticipatory task-set reconfiguration processes. In this study, the switch-related positivity was examined in a cued task-switching paradigm. Cue-stimulus and response-stimulus intervals were independently manipulated to dissociate between the effects of anticipatory preparation and passive dissipation of task-set interference. Reaction time switch cost declined with increasing cue-stimulus and response-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

40
229
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(274 citation statements)
references
References 38 publications
(80 reference statements)
40
229
5
Order By: Relevance
“…Consistent with the claim that the task-cuing paradigm entails task switching in addition to cue switching, a number of recent ERP studies using the 2: I cue-to-task mapping procedure (e.g., Jost et aI., 2008;Lavric et aI., 2008;Nicholson et aI., 2006) showed that the larger parietal positivity that is usually observed for switch trials compared with repetition trials during the prepa-ratory interval (e.g., Karayanidis et aI., 2003;Miniussi, Marzi, & Nobre, 2005;Nicholson, Karayanidis, Poboka, Heathcote, & Michie, 2005;Wylie, Javitt, & Foxe, 2003) primarily refers to task switches rather than cue switches. Nicholson et al (2006) used two different cues per task, a color cue and a form cue, to indicate the required task (magnitude or parity judgment).…”
Section: Preparation As Interaction Of Cue Encoding and Memory Retrievalmentioning
confidence: 99%
“…Consistent with the claim that the task-cuing paradigm entails task switching in addition to cue switching, a number of recent ERP studies using the 2: I cue-to-task mapping procedure (e.g., Jost et aI., 2008;Lavric et aI., 2008;Nicholson et aI., 2006) showed that the larger parietal positivity that is usually observed for switch trials compared with repetition trials during the prepa-ratory interval (e.g., Karayanidis et aI., 2003;Miniussi, Marzi, & Nobre, 2005;Nicholson, Karayanidis, Poboka, Heathcote, & Michie, 2005;Wylie, Javitt, & Foxe, 2003) primarily refers to task switches rather than cue switches. Nicholson et al (2006) used two different cues per task, a color cue and a form cue, to indicate the required task (magnitude or parity judgment).…”
Section: Preparation As Interaction Of Cue Encoding and Memory Retrievalmentioning
confidence: 99%
“…Without the subtraction procedure, amplitudes for fast and slow trials already differed substantially before and following signal onset. For the quantification of N2 amplitudes we therefore baseline corrected amplitudes to the interval from 50 ms before to 50 ms after signal onset 5 (see e.g., Karayanidis, Coltheart, Michie & Murphy, 2003;Nicholson, Karayanidis, Bumak, Poboka & Michie, 2006;Nicholson, Karayanidis, Poboka, Heathcote & Michie, 2005, for a similar approach). P3 amplitudes, averaged over electrodes FCz, Cz and Pz, were quantified as the N2 to P3 difference.…”
Section: Eeg/erps the Electroencephalogram (Eeg) Was Acquired Using 64mentioning
confidence: 99%
“…In addition, the dynamics of this frontoparietal network have also been studied using ERPs and magnetoencephalographic (MEG) recordings, which revealed an amplitude enhancement of a frontoparietal P3-like component in response to signals indicating the need of a task switch (Barceló, Periañez, & Knight, 2002;Furumoto, 1991;Periáñez et al, 2004;Stuss & Picton, 1978;Watson, Azizian, & Squires, 2006). Accordingly, many authors have interpreted the switch-P3 enhancement in the ERPs as the neural signature of a cognitive control mechanism required for task set reconfiguration during task switching (Brass, Ullsperger, Knoesche, von Cramon, & Phillips, 2005;Kieffaber & Hetrick, 2005;Kopp, Tabeling, Moschner, & Wessel, 2006;Lai & Mangels, 2007;Nicholson, Karayanidis, Poboka, Heathcote, & Michie, 2005;Rushworth, Passingham, & Nobre, 2002;Slagter, Kok, Mol, Talsma, & Kenemans, 2005;Swainson, Jackson, & Jackson, 2006).…”
Section: Introductionmentioning
confidence: 99%